2017
DOI: 10.3892/mmr.2017.7708
|View full text |Cite
|
Sign up to set email alerts
|

WWC1 promotes podocyte survival via stabilizing slit diaphragm protein dendrin

Abstract: Previous studies have indicated that glomerular podocyte injury serves a crucial role in proteinuria during the process of chronic kidney disease. The slit diaphragm of podocytes forms the final barrier to proteinuria. Dendrin, a constituent of the slit diaphragm protein complex, has been observed to relocate from the slit diaphragm to the nuclei in injured podocytes and promote podocyte apoptosis. However, the exact mechanism for nuclear relocation of dendrin remains unclear. The expression of WWC1 in podocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…Actually, recent basic and clinical research has also indicated that the nuclear translocation of dendrin induces podocyte apoptosis. [46][47][48][49] Additionally, other groups also demonstrated that MAGI-2 is a key molecule of Rap1 signaling, which is related to actin remodeling and secretion. 27 Taken together, MAGI-2 has three important functions for maintaining the filtration barrier: preventing podocyte apoptosis, regulating Rap1 signaling and stabilizing SD proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, recent basic and clinical research has also indicated that the nuclear translocation of dendrin induces podocyte apoptosis. [46][47][48][49] Additionally, other groups also demonstrated that MAGI-2 is a key molecule of Rap1 signaling, which is related to actin remodeling and secretion. 27 Taken together, MAGI-2 has three important functions for maintaining the filtration barrier: preventing podocyte apoptosis, regulating Rap1 signaling and stabilizing SD proteins.…”
Section: Discussionmentioning
confidence: 99%
“…WW domain-containing protein 1 (WWC1), also known as kidney and brain scaffolding protein (KIBRA), is predominantly expressed in the kidney [ 47 ]. The knockdown of WWC1 in an in vitro model promoted podocyte apoptosis by inducing nuclear relocation of dendrin protein [ 48 ] and impaired directed cell migration [ 49 ]. Conversely, KIBRA has also been shown to promote podocyte injury by inhibiting YAP signaling, by disrupting actin cytoskeletal dynamics [ 50 ], and by interacting with synaptopodin [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Synaptopodin (SYNPO) is a 929-residue proline-rich actin cytoskeleton-associated protein, found in kidney podocytes and the dendrites of neurons (1,(20)(21)(22). In kidney podocytes, it is essential for the integrity of the podocyte actin cytoskeleton (23,24) and forms a WW domain-PPXY-mediated complex with KIBRA implicated in cell migration (4).…”
mentioning
confidence: 99%